Upaya Pemerintah Desa terhadap Kebijakan Pembatasan Sosial Berskala Besar di Desa Jatibaru Lampung Selatan - Setiyana, Norma; Hakim, Dani Amran (As-Siyasi: Journal of Constitutional Law, 2021)
Based on Government Regulation Number 21 of 2020 concerning Large-Scale Social Restrictions in the Context of Accelerating the Handling of Corona Virus Disease 2019, it is hoped that it can suppress the spread of Covid-19. The implementation of these regulations certainly takes into account the situation and condition of an area. The method used is a descriptive qualitative field research. The analysis used is descriptive analysis method. The efforts made by Jatibaru Village, South Lampung Regency, have been implemented through the South Lampung Regent Circular Number: 442.2/0994/IV.02/2020 concerning Prevention of Corona Virus Disease (Covid-19) South Lampung Regency. The circular contains steps that must be taken in response to the development of the spread of Covid-19. These measures include school holidays, the establishment of a Covid-19 task force, postponement of activities that involve large numbers of people, providing hand washing facilities and hand sanitizers, as well as appeals to the public not to panic and continue to practice clean and healthy lifestyles. The circular letter is also a response from the regional government to Government Regulation Number 21 of 2020 concerning Large-Scale Social Restrictions or PP 21/2020 PSBB.